Anti‐obesity effects of Chenpi: an artificial gastrointestinal system study. Issue 3 (16th February 2022) - Falduto, Maria; Smedile, Francesco; Zhang, Man; Zheng, Ting; Zhu, Jieyu; Huang, Qingrong; Weeks, Richard; Ermakov, Alexey M.; Chikindas, Michael L.
Summary: The gut microbiota plays a significant role in human health; however, the complex relationship between gut microbial communities and host health is still to be thoroughly studied and understood. Microbes in the distal gut contribute to host health through the biosynthesis of vitamins and essential amino acids and the generation of important metabolic by‐products from dietary components that are left undigested by the small intestine. Aged citrus peel (Chenpi) is used in traditional Chinese medicine to lower cholesterol, promote weight loss and treat various gastrointestinal symptoms. This study investigated how the microbial community changes during treatment with Chenpi using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME). Two preparations of Chenpi extract were tested: Chenpi suspended in oil only and Chenpi in a viscoelastic emulsion. Short‐chain fatty acids (SCFAs) were measured during treatment to monitor changes in the microbial community of the colon presenting a decrease in production for acetic, propionic and butyric acid (ANOVA ( P < 0.001) during the 15 days of treatment. 16S rRNA sequencing of microbial samples showed a clear difference between the two treatments at the different sampling times (ANOSIM P < 0.003; ADOSIM P < 0.002 [ R 2 = 69%]). Beta diversity analysis by PcoA showed differences between the two Chenpi formulations for treatment day 6. These differences were no longer detectable as soon as the Chenpi treatment was stopped, showing a reversible effect of Chenpi on the human microbiome. 16S rRNA sequencing of microbial samples from the descending colon showed an increase in Firmicutes for the treatment with the viscoelastic emulsion. At the genus level, Roseburia, Blautia, Subdoligranulum and Eubacterium increased in numbers during the viscoelastic emulsion treatment. This study sheds light on the anti‐obesity effect of a polymethoxyflavone (PMFs)‐enriched Chenpi extract and creates a foundation for the identification of 'obesity‐prevention' biomarkers in the gut microbiota. Abstract : This study investigated how the microbial community changes during treatment with Chenpi using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) and two preparations of Chenpi extract were tested: Chenpi suspended in oil only and Chenpi in a viscoelastic emulsion. Short‐chain fatty acids (SCFAs) were measured during treatment to monitor changes in the microbial community of the colon presenting a decrease in production for acetic, propionic and butyric acid (ANOVA ( P < 0.001) during the 15 days of treatment. 16S rRNA sequencing of microbial samples from the descending colon showed an increase of Firmicutes for the treatment with the viscoelastic emulsion.